Parallel Control Method of Microgrid Inverter Based on Adaptive Droop Control. (June 2020) - Hu, Linlin; Guan, Jian; Fu, Long
Abstract: Energy is the driving force of social and economic development. With the gradual depletion of conventional energy and the increasingly prominent ecological and environmental problems, the power industry needs to find a sustainable development path. Parallel control of microgrid inverters based on adaptive droop control is an important part of future intelligent and sustainable power systems. However, with the continuous increase of power generation equipment capacity and the continuous increase of load power consumption, the form of power supply by a single inverter can no longer meet the requirements. Therefore, parallel connection of multiple inverters has been widely used in the microgrid. In this paper, a set of parallel control methods for microgrid inverters based on adaptive droop control is established. This paper is based on the inductance of the inverter's terminal impedance, and the amplitude of the inverter terminal voltage is positively correlated with the output reactive power and has a strong correlation It is concluded that the microgrid based on adaptive droop control has the ability to automatically adjust the voltage and frequency of the microgrid. Properly reducing the droop coefficient can improve the primary frequency modulation capability of the microgrid. In this paper, an improved resistive control equation is used in a parallel system, a multi-loop control structure with a quasi-resonant controller is used for the inverter in the parallel system, and a virtual complex impedance is added to perform small signal analysis on the improved resistive control equation The overall performance of the parallel system is analyzed, and the effect of different control coefficients on the system performance is clarified. The experimental research results show that when analyzing the effect of the inductance coefficient value on the equivalent output impedance in the virtual complex impedance, the value of KL is 1 At this time, the equivalent output impedance becomes resistive again, and the property is stronger than when KL is 0.05.